2024
DOI: 10.3390/ijms25073969
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targets of Novel Therapeutics for Diabetic Kidney Disease: A New Era of Nephroprotection

Alessio Mazzieri,
Francesca Porcellati,
Francesca Timio
et al.

Abstract: Diabetic kidney disease (DKD) is a chronic microvascular complication in patients with diabetes mellitus (DM) and the leading cause of end-stage kidney disease (ESKD). Although glomerulosclerosis, tubular injury and interstitial fibrosis are typical damages of DKD, the interplay of different processes (metabolic factors, oxidative stress, inflammatory pathway, fibrotic signaling, and hemodynamic mechanisms) appears to drive the onset and progression of DKD. A growing understanding of the pathogenetic mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…The cellular signaling responses include growth factor signaling, the response to nitric oxide, the response to oxidative stress, the cytokine response, macrophage signaling, the TLR pathway, the T-cell-mediated response, NFκB factor activity, ERK/MAPK signaling, the JAK/STAT pathway, the WNT/β-catenin pathway, and NADPH oxidase activity. Several of these pathways are known to be implicated in GEC injury, inflammation, and fibrosis associated with DKD [6,8,11,17]. Similarly, the analyses suggested that the apoptotic processes, the response to cytokines, the T-cell-mediated response, the immune response, calcium channel activity, and growth factor signaling were the most frequent and active biological processes in DKD (Figures 6 and 7).…”
Section: Top-ranked Intersecting Cellular Functions and Signaling Pro...mentioning
confidence: 81%
See 3 more Smart Citations
“…The cellular signaling responses include growth factor signaling, the response to nitric oxide, the response to oxidative stress, the cytokine response, macrophage signaling, the TLR pathway, the T-cell-mediated response, NFκB factor activity, ERK/MAPK signaling, the JAK/STAT pathway, the WNT/β-catenin pathway, and NADPH oxidase activity. Several of these pathways are known to be implicated in GEC injury, inflammation, and fibrosis associated with DKD [6,8,11,17]. Similarly, the analyses suggested that the apoptotic processes, the response to cytokines, the T-cell-mediated response, the immune response, calcium channel activity, and growth factor signaling were the most frequent and active biological processes in DKD (Figures 6 and 7).…”
Section: Top-ranked Intersecting Cellular Functions and Signaling Pro...mentioning
confidence: 81%
“…The pathophysiology of DKD is multi-factorial and characterized by metabolic impairment, an uncontrolled inflammatory response, increased apoptosis, and tissue fibrosis [4,6]. In diabetes, aberrant glucose metabolism leads to dysregulation of the immune response and signaling [6][7][8]. Metabolic abnormalities activate the mononuclear phagocyte system, which releases pro-inflammatory cytokines and paracrine signals, leading to immune cell infiltration [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations